Heat transfer : - Cengel, Yunus A. (McGraw-Hill, 1997)
The text covers the basic principles of heat transfer with a broad range of engineering applications. It contains sufficient material to give instructors flexibility and to accommodate their preferences on the right blend of fundamentals and applications.